Permasalahan Hukum Seputar Penertiban Juru Parkir Tidak Resmi di Kota Samarinda - Maria Nuansa Nogo Hekar; Insan Tajali Nur; Orin Gusta Andini (Jurnal Ilmu Sosial dan Humaniora, 2023)
The aim of this research is to control illegal parking attendants in a humane manner, namely the control carried out by DISHUB and SATPOL PP. The research approach was carried out using a social legal approach, aiming to examine two main points of discussion, namely analyzing the obstacles faced in controlling unofficial parking attendants in Samarinda City and finding out the legal efforts taken to overcome the problem of unofficial parking attendants in Samarinda City. The results of the research show that the obstacles faced originate from the regional government which has not yet optimally implemented non-penal measures in regional legal products related to controlling unofficial parking attendants in Samarinda City, law enforcement has not yet found a preventative solution, and public awareness regarding traffic order is still lacking. The legal remedies taken are in the form of non-penal legal remedies using a humanist approach, as well as penal legal remedies. as stated in Article 22 of the Samarinda City Regional Regulation Number 5 of 2015, Article 50 paragraph (1), Article 57 paragraph (1), and Article 268 paragraph (1) of the Criminal Code